I’m assuming what you’re asking here is how to *factor* this expression. For that, let’s rearrange the expression into a more familiar form:
-c^2-4c+21
From here, we’ll factor out a -1 so that we have:
-(c^2+4c-21)
Let’s focus on the quadratic expression inside the parentheses. To find our factors (c + x)(c + y), we’ll need to find two terms x and y that multiply together to make -21 and add together to make 4. It turns out that the numbers -3 and 7 work out perfectly for that purpose (-3 x 7 = -21 and 7 + (-3) = 4), so substituting them in for x and y, we have:
(c + (-3))(c + 7)
(c - 3)(c + 7)
And adding back on the negative from a few steps earlier:
-(c - 3)(c + 7)
Answer:
.5? or 1/2
Step-by-step explanation:
i think its half, because the Y factors are going down by half.
i hope that kinda made sense.
43 divided by 50 equals to 0.86
Answer:-35
Step-by-step explanation:
To find 55 more a number equal to 20
We get
Let the number b y
55 more than the number
We be
y+55=20
y=20-55
y=-35
Answer:
The answer is B.(5,10)
Step-by-step explanation:
1. y = 2(5)
y = 10
2.y = -2(5)+20
y = -10+20
y = 10